2002
DOI: 10.1002/qua.10423
|View full text |Cite
|
Sign up to set email alerts
|

Chemical model for superconductivity

Abstract: ABSTRACT:A "chemical" model based on the theory of mixed valence systems is successful in explaining a number of properties of superconductors. The model is formulated in configuration space but is consistent with Bardeen-Cooper-Schrieffer theory, and connects directly to chemical properties that may be calculated by quantum chemical methods. Crystal structure is important, in particular the difference in equilibrium geometry between different oxidation states. According to the model, high pressure causes less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 112 publications
(142 reference statements)
1
4
0
Order By: Relevance
“…Lattice distortion versus coupling is. As has been shown in previous articles 19, 25, 26, 32–34, the coupling may very well “cancel out” the trapping forces of lattice distortion, thereby implying a free bipolaron. Contrary to the conclusions of Chakraverty et al 53, delocalization of the bipolaron is possible under special circumstances.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Lattice distortion versus coupling is. As has been shown in previous articles 19, 25, 26, 32–34, the coupling may very well “cancel out” the trapping forces of lattice distortion, thereby implying a free bipolaron. Contrary to the conclusions of Chakraverty et al 53, delocalization of the bipolaron is possible under special circumstances.…”
Section: Discussionsupporting
confidence: 52%
“…We will use as a fundamental condition for itinerancy that the pair moves without activation energy. This problem is part of the well understood MV models 20–26. The same theory that applies to cuprates applies to a number of other systems as well 26, 32–34.…”
Section: Introduction: Historical Notesmentioning
confidence: 97%
See 1 more Smart Citation
“…The anisotropic carrier-phonon coupling, reaching its maximum along the CuOO bond, and the distortion of the CuOO planes, suggest a direct role for structural dynamics and considerations (41)(42)(43) beyond simple 2D models. Recent theoretical work has incorporated lattice phonons in the t-J model to account for the observed optical conductivity (44), whereas new band structure calculations suggested that large and directional electron-phonon coupling can favor spin ordering (45).…”
Section: Resultsmentioning
confidence: 99%
“…Cooper's discussion [10] of the motion of electron pairs in interaction with phonons led to the development of the BCS theory, which has introduced great clarification in the field of superconductivity [9]. Electron pairs of the BCS theory (Cooper pairs) are appealing to chemists because there is no reason to believe electron pairs in superconductors should differ greatly from electron pairs in other systems, particularly the mixed valence systems where difference between oxidation states must be two units-given that at least two electrons are involved in each elementary charge transfer step [10,11]. In RVB theory, the electronic structure of the superconductor is described in successive steps that involve integrals of decreasing magnitude.…”
mentioning
confidence: 99%